Work Accident Risk Analysis in Water Treatment Plant Laboratory of PT XYZ using JSA and HIRARC Methods - Azumah Islahiyah; Moh. Jufriyanto (G-Tech: Jurnal Teknologi Terapan, 2025)
PT. XYZ produces fertilizers and chemicals for agro-industrial solutions. To maintain product quality, quality control is carried out in the water treatment laboratory. The increasing complexity of laboratory activities increases the risk of workplace accidents, such as inhaling reactive chemicals that can irritate the respiratory system and cause poisoning, or slipping while taking samples, which can cause injury. This study aims to analyze potential hazards and design control recommendations using the Job Safety Analysis (JSA) and Hazard Identification, Risk Assessment, and Risk Control (HIRARC) methods. Data were collected through interviews with employees and questionnaires assessing the likelihood and severity of hazards. The results of the study identified 12 potential hazards spread across 4 work activities. There were 2 very high-level hazards, 9 high-level hazards, and 1 moderate-level hazard. This study provides control recommendations to reduce risks, such as controls including the use of appropriate Personal Protective Equipment (PPE) etc., thereby supporting improved workplace safety at the PT. XYZ laboratory.